Utilization Public Relations Fanpage of the Governor of North Sumatra in Increasing Public Awareness and Participation - Kurniawati, Dewi; Safrin, Safrin (Journal of Social Interactions and Humanities, 2024)
Technological developments can not only help to communicate but can also help in disseminating information to the public. Through the delivery of information, we can see the response of the people who receive it. Utilizing the development of communication technology makes it easier to convey information so that it can increase awareness and invite people to participate through social media. This research was conducted to increase public awareness and participation in information notifications provided by the Public Relations of the Governor of North Sumatra through Fanpage. The research method used was a quantitative descriptive study conducted in 3 regions, namely Deli Serdang Regency, Medan City and Binjai City (Mebidang). This study in determining the sample using purposive sampling technique by using a sample quota of 100 respondents at each research location so that the total number of respondents was 300 respondents.The results showed that the people of North Sumatra responded quite well to information on North Sumatra government activities delivered through Fanpage and the content of the message was able to increase public awareness and participation in development programs.The community provided input so that more diverse information about development programs carried out by the North Sumatra government and the message content was not monotonous.